Behind the blackboard: reviewing educators’ experiences of school violence in South Africa - Mottee, Cara Le (Acta criminologica, 2017)
No school is exempt from violence. Consequently, school safety is identified as a topic of great concern on both a national and international level. While this has resulted in a significant focus on learners’ safety in schools, relatively little attention has been given to violence against, and safety of, the educators in the school environment. Educator victimisation, in various forms, may be a notable problem. However, the true extent is unknown, due to issues such as general underreporting of such incidents, and insufficient research on the topic. This article takes a closer look at the nature and extent of the safety issues faced by educators, and the numerous implications which may result from this, including the negative impact it has on not only the educators themselves, but on the education system as a whole. There are various factors which contribute to violence against educators, and through the examination of these issues, rights and responsibilities come to the fore as a main theme - specifically those held by educators and learners, and the conundrum often created in trying to balance these. This is important both in beginning to understanding the problem, as well as formulating a set of relevant, comprehensive recommendations for moving forward, and finding a solution in the creation of a culture of human rights, as opposed to a culture of violence.